A Growth Curve Model for CO2 Emissions in G19 Countries - Kharbach, Mohammed; Belakhdar, Adnan; Chfadi, Tarik (International Journal of Energy Economics and Policy, 2021)
CO2 emissions per capita (Emc) and CO2 emissions intensity (Emint) are among the main metrics used to report emissions in environmental studies. The main aim of this note is to compare the evolution of Emc and Emint in the G19 countries. Comparing their varying trends is useful in benchmark analysis. Indeed, in our study of the G19 countries, we offer evidence that such metrics show different trends for the same group of countries both at the sample and the individual level. Using a growth curve modeling approach, we find that Emint has been decreasing in the G19 countries while Emc has been increasing, but at a slower pace. Further, countries with high initial Emint have achieved the greatest reduction in the period analyzed, whereas there is no evidence of such a change in the case of countries with high initial Emc. We also find that a country’s area affects its Emint growth, but not its Emc. Used together, Emint and Emc offer better insights into environmental performance as measured through these metrics. Keywords: Emissions intensity; Emissions per capita; growth curve model; G19; CO2 reduction JEL Classifications: C15, Q53, Q56 DOI: https://doi.org/10.32479/ijeep.9725